2006
DOI: 10.1016/j.cmet.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y5 receptor antagonism does not induce clinically meaningful weight loss in overweight and obese adults

Abstract: Neuropeptide Y (NPY) is a potent orexigenic neuropeptide, and antagonism of NPY Y1 and NPY Y5 receptors (NPYxR) is considered a potentially important anti-obesity drug target. We tested the hypothesis that blockade of the NPY5R will lead to weight loss in humans using MK-0557, a potent, highly selective, orally active NPY5R antagonist. The initial series of experiments reported herein, including a multiple-dose positron-emission tomography study and a 12 week proof-of concept/dose-ranging study, suggested an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 44 publications
4
131
0
3
Order By: Relevance
“…8a Recently, it was reported that administration of a potent and highly selective NPY Y5 receptor antagonist, MK-557, resulted in modest weight loss in obese human subjects. 12 Considering the well-tolerated Y5 antagonist treatment in humans and possibility of the combination therapy with Y1 antagonists, development of safe and mechanistically validated Y5 antagonists is of considerable importance. 11d We previously reported the discovery of a potent imidazoline class of Y5 antagonists, 1a and 1b ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…8a Recently, it was reported that administration of a potent and highly selective NPY Y5 receptor antagonist, MK-557, resulted in modest weight loss in obese human subjects. 12 Considering the well-tolerated Y5 antagonist treatment in humans and possibility of the combination therapy with Y1 antagonists, development of safe and mechanistically validated Y5 antagonists is of considerable importance. 11d We previously reported the discovery of a potent imidazoline class of Y5 antagonists, 1a and 1b ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some Y5 receptor antagonists have been tested in humans. The orally active Y5 receptor antagonist MK-0557 induced weight loss statistically greater than placebo control after one year of treatment, but the magnitude of this effect was not clinically meaningful [23]. The orally active Y5 receptor antagonist S-2367 resulted in a small reduction in body weight compared to placebo-treated controls when administered to obese subjects in conjunction with a 500-800 kcal/day energy deficit [22].…”
Section: Neuropeptide Ymentioning
confidence: 99%
“…The Y5 antagonist MK0557 was recently shown to induce only modest weight loss (3.4 kg) compared with placebo (1.8 kg) in a 52-week study. These results led the authors to conclude that Y5 receptor activation is involved in energy homeostasis in man; however, selective blockade of this receptor alone was insufficient to produce clinically meaningful weight loss [47].…”
Section: Neuropeptide Y Antagonistsmentioning
confidence: 99%
“…NPY levels are regulated by leptin and other peripheral modulators (e.g. gut hormones); following a meal when leptin levels are low,NPY activity is reduced [47].Conversely, NPY levels are elevated during hunger and energy depletion [21]. Selective NPY antagonists, particularly targeting NPY5 receptors, inhibit feeding and reduce body weight in models of obesity [46].…”
Section: Neuropeptide Y Antagonistsmentioning
confidence: 99%